Against aging - Rudim, Deanne; Qamaruz Zaman, Faridah (University Putra Malaysia, 2012)
Aging refers to the age-related changes in body and behavior after maturity. It is characterized by losses: structures decaying and functions deteriorating. Free radicals are responsible in accelerating the aging process and causing various human age-related conditions such as arthritis, hypertension and heart disease. However, free radicals can be neutralized by means of antioxidants. Antioxidant is the substance which is able to inhibit or delay the oxidative damage caused by free radicals and these properties are exhibited by a number of phenolic compounds. In short, antioxidant properties exhibited by phenolic compounds effectively neutralize free radicals and delay or reverse aging